Edukasi diabetes pada remaja sebagai upaya pemeliharaan kesehatan remaja - Halimatushadyah, Ernie; Lukitasari, Nurraya; Yuliana, Agnes; Putri, Dinda Widia Aprilina; Suharto, Muhammad Aldila (Nur Science Institute, 2025)
Diabetes mellitus (DM) is a chronic disease caused by the inability of the body to produce sufficient insulin or to use insulin effectively. The prevalence of diabetes among young people in Indonesia, based on doctor diagnoses, remained unchanged from 2013 to 2018 (0.5%). However, the percentage of young diabetes patients who do not receive treatment is 18.5% (highest). Young adults also represent the age group with the highest percentage of individuals who have never had their blood sugar levels checked (86.6%). This activity aims to provide adolescents with basic knowledge about the definition of diabetes, available therapies for young diabetes patients, and preventive measures. The method used in this community service activity involved delivering material in person and distributing brochures on diabetes prevention among adolescents at SMK Bhumi Husada. The target participants were adolescents aged 17–19 years. The activity proceeded smoothly, and the students comprehended the educational material provided. Adolescents gained an understanding of diabetes prevention, leading to healthier lifestyle behaviors.